Socio-ecological determinants of alcohol, tobacco, and drug use behavior of adolescents in Kilifi County at the Kenyan coast - Ssewanyana, D; Mwangala, P; Marsh, V; Jao, I; Van Baar, A; Newton, C; Abubakar, A (SAGE Publications, 2018)
Alcohol, tobacco, and other drug use form a risk factor for health and social problems during adolescence. From a socio-ecological model, perceptions of 85 young people and 10 stakeholders on the types of alcohol, tobacco, and other drugs used and the predisposing and protective factors were explored; among adolescents at the Kenyan Coast in the Kilifi County. We found that the consumption of home-brewed alcohol, tobacco and marijuana smoking, and khat chewing was common and requires multi-component and community-centered intervention. Countering alcohol, tobacco, and other drug use needs enforcement of strong measures to regulate access to alcohol, tobacco, and other drugs for minors; addressing social and cultural norms; strategies for poverty alleviation; and community empowerment.